Pilot implementation outcomes of a community-based tele- practice model for identification and rehabilitation of children with hearing loss within a public-health system of a Rural District in Southern India - Karishmaa Satheesh; Vidya Ramkumar; Deepashree Joshi; Bommi E. (PLoS ONE, 2025)
Background The current study is an effort to evaluate pilot outcomes of a comprehensive tele-practice model for identification and rehabilitation of hearing loss among children below six years of age, which can then inform suitable adaptations prior to the implementation. The outcomes of tele-facilitator training, limited-efficacy measures, and caregiver acceptability and satisfaction with tele-practice were analyzed. Method Two special educators were trained as tele-facilitators for tele-diagnostic testing. Screening was done using the validated SRESHT screener in the Perambalur district by trained nurses in the Upgraded Primary Healthcare Centers at all four blocks until at least five children with ‘refer’ results were obtained. For tele-rehabilitation, we enrolled five children with hearing loss who used amplification devices and attended the District Early Intervention Centre. To measure the limited- efficacy, the outcomes of pre-pilot and post-pilot were compared. The caregiver acceptability and satisfaction with tele-practice were also assessed. Results In all 12 children (age range of 5 months to 6 years; 6 male and 6 female) with ‘refer’ results in hearing screening underwent tele- diagnostic testing. Tele-rehabilitation outcomes were studied on 5 children with hearing loss (age range of 4 years to 6 years; 3 male and 2 female) who had already used amplification devices. When comparing the outcomes of limited-efficacy with the existing data, it was found that the model identified older children with hearing loss. The time lapse between screening/hearing loss suspicion and diagnosis reduced from a median of 216 days to eight days. For tele-rehabilitation, the number of sessions attended in a span of three months increased from a median of zero to three sessions. Based on the satisfaction questionnaire, most people had a positive experience and found the travel time to the testing site convenient and affordable. Few parents reported encountering difficulties as a result of inadequate ventilation and internet connectivity within the mobile van where tele-diagnostic testing was conducted. Conclusion The pilot outcomes suggest that a block-level service enabled using tele-practice to overcome professional shortages was beneficial in reducing time gap between screening/suspicion and diagnosis and also enhanced attendance for rehabilitation. The pilot outcomes provided insights on adaptations related to screening sites, test infrastructure, and internet optimization that may be required before implementation.